Ayn Rand and the posthuman : the mind-made future - Murnane, Ben (Trinity College (Dublin, Ireland). School of English, 2016)
American novelist Ayn Rand's documented influence on politicians, economists, and businesspeople, makes her work an ideal case study for fiction's impact on society. This thesis considers Rand’s veneration of technological advancement, and how her work relates to various conceptions of the future - both fictional and nonfictional. In the process, I demonstrate Rand's connection to those with a “posthuman” vision, in which human and machine merge. Posthumanism is a concept of subjectivity driven by our continuing interdependence with technology; it is therefore likely to remain important as the twenty-first century continues. My thesis is an analysis of one of the twentieth century’s most influential authors in the light of one of the major theories of twenty-first-century subjectivity.
Embargo End Date: 2023-07-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2016